Employee Motivation as an Element of the Development Process in an Enterprise - Kozłowski, Waldemar (Olsztyn Economic Journal, 2020)
Motivation is one of the most important elements from an enterprise development perspective which, in turn, provides a basis for the development of other strategic perspectives. However, several barriers may distort the positive correlation between staff motivation and the development perspective of the enterprise. The research problem concerns the location of employee motivation in the development perspective as one of the key elements of the strategic scorecard. The research objectives within the research problem are the analysis of the level of employee motivation and the correlation of the level of motivation with the results of the organization. The aim of the article is to analyze the level of motivation of employees in a production and trade company. The subject of research is the motivational system. The basic research method was a survey. The research results demonstrated which elements of the motivational process, and to what extent, should be analysed and improved, as required by the evaluation. There exists a close relationship between employee motivation and the perspective of internal processes, the client’s perspective and, consequently, the financial perspective.